The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.5334/ijic.5599
|View full text |Cite
|
Sign up to set email alerts
|

Developing Interpersonal Trust Between Service Users and Professionals in Integrated Services: Compensating for Latent Distrust, Vulnerabilities and Uncertainty Shaped by Organisational Context

Abstract: Introduction: Studies show a need for trust between stakeholders in integrated services. However, few studies have investigated how trust develops between stakeholders on a micro-level. In a Danish intersectoral intervention for persons on sick leave due to common mental disorders, we explored why trust is needed and how trust is developed between micro-level stakeholders. Methodology: The qualitative study was based on 12 observations of inter-organisational meetings, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Trust has also a context-specific cognitive dimension, meaning that people have beliefs and make decisions about whom to trust and when. For example, the specific actions that people believe contribute to trust in the context of authorities are different from those in the community or in the context of personal relationships [ 41 ]. Accordingly, the same trust-building strategies do not apply to both.…”
Section: Discussionmentioning
confidence: 99%
“…Trust has also a context-specific cognitive dimension, meaning that people have beliefs and make decisions about whom to trust and when. For example, the specific actions that people believe contribute to trust in the context of authorities are different from those in the community or in the context of personal relationships [ 41 ]. Accordingly, the same trust-building strategies do not apply to both.…”
Section: Discussionmentioning
confidence: 99%
“…As these two parts of the intervention were only part of INT, we can conclude that only interventions in the MHC group were implemented with high fidelity. True integration of the intervention components in INT was challenged by lack of trust and diverging norms and goals between the different sectors, as described elsewhere (12,13). In other studies, VR services similar to IBBIS-VR have shown positive effect.…”
Section: Hoff Et Almentioning
confidence: 95%